Domestic Violence, Mental Health, and COVID-19: A Community-based Study of Women in Delhi - Ajit Kumar Lenka; Neha Sharawat; Smritima Diksha Lama; Sanghmitra S Acharya (Social Work and Society)
Domestic violence is a product of unequal gender power relations in the household. During the COVID-19 pandemic, due to restricted physical movement there was an increased risk of violence which further exacerbated the vulnerability of those already in abusive relationships. Several factors led to an increase in the number of domestic violence cases including loss of livelihoods, restriction of social contact within informal and informal networks, and limited access to services and community support. During the COVID-19 in many countries, data indicates an increase in reports of domestic violence, sexual harassment, and other forms of violence against women. The current paper is based on an empirical study using qualitative methods of data collection, conducted in Munirka urban village, Delhi. The paper focuses on the factors affecting the rate of increase in domestic violence cases during the COVID-19 pandemic, and subsequent effects on the mental health of women. Main finding of the study indicates that cases of domestic violence during COVID-19 increased due to alcoholism, loss of livelihood, financial insecurity, and limited access to services. Hence, authors suggest that to reduce the prevalence of violence against women, there should be an improvement in female education, raising awareness about their rights, and providing better social support.